Gambaran Darah dan Histopatologi Insang, Usus Dan Otak Ikan Koi (Cyprinus carpio Koi) yang Diinfeksi Spora Myxobolus koi secara Oral [Haematology and Histopatology of Gills, Intestine And Brain Koi Fish (Cyprinus carpio Koi) Myxobolus koi Orally Infected] - Gunanti Mahasri; Kusnoto Kusnoto; Era Insivitawati (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Koi fish (Cyprinus carpio koi) is one of the ornamental fish are preferred. One of the obstalces in the koi fish is a disease caused by infection myxobollus. This research to determine the effect of the infection myxobollus by oral in blood picture and histopathology. Haematology and histopathology is an indicator of the health of the fish to diagnose disease and to determine changes in the fish tissue. The research was conducted in Politeknik Kelautan dan Perikanan, dan Balai Karantina Ikan Kelas I, Juanda Surabaya from October to December 2014. This study uses the 5 treatments and 5 replications with different doses of infection (0,60,80,100 and 120 spora/fish). Data were analyzed with Annova haematology, followed by Duncan 5%. While histopathology were analyzed by semiquantitative scoring mothod used to determine the degree of histology Kluschal Wallis. The result showed that the haematology has significant result, white histopathology signify the presence of significant damage.